A Study of Moral Judgment of School Children Belonging to Different Socio-Economic Status and School Backgrounds - Singh, Pawan Kumar (International Multidisciplinary Research Journal, 2011)
<div style="border-right: medium none; padding-right: 0in; border-top: windowtext 1pt solid; padding-left: 0in; padding-bottom: 0in; margin-left: 34pt; border-left: medium none; margin-right: 34pt; padding-top: 1pt; border-bottom: medium none; mso-element: para-border-div; mso-border-top-alt: solid windowtext .5pt;"> The national education policy (1986) lays emphasis on moral and social values and therefore the teachers are induced to, themselves, become morally handsome and impart moral education to the children through their deeds. We could ensure social harmony, peace, love and brotherhood, by cultivation of moral values among the children. Two hundred students have been selected in the sample by using stratified random sampling technique. In case of convent background schools, students of low S.E.S. group have shown better moral judgment than the students of high S.E.S. group. There exists no significant difference in the moral judgment of high and low S.E.S. group students of Nagar Palika background schools.